Empowerment of Lurik Batik Craftsmen through One Village One Product (OVOP) Approach to Increase Community Revenues in Central Java Province - Risca Cynthiana Sugiyarwati (Institut Pemerintahan Dalam Negeri (IPDN), 2017)
The tittle of this research is the Empowerment of Batik Lurik Craftsmen through One Village One Product (OVOP) Approach in Increasing the Income of Villagers of Jambakan, Bayat Sub-District, Klaten Regency, Central Java Province. Modern Batik handcraft increaseing in Central Java pressing Batik Lurik which is traditional Batik from Klaten Regency. The production of Batik Lurik still using traditional method ATBM (No Machine Tenun Tool) and must through 5 steps dan it takes long times and it makes reducing public interest to become a craftsmen and it result limited Lurik Batik production. Results showed that the empowerment of batik lurik craftsmen through One Village One Product (OVOP) approach in increasing the income of the people of Jambakan Village, Bayat Sub-district, Klaten Regency has been implemented quiet optimal. As proved by the following aspects: 1. Possibility, realization of stable economic situation and encouraging the development of Batik Lurik; 2.affirmation, has been as the implementing of training programs for improving the quality of human resources; 3. Protection, the establishment of the product of local law as a form of protection of local products; 4. Supporting, the implementation of the provision of capital assistance and equipment assistance for the craftsmen even though Batik Lurik is limited; And 5. Maintenance, the implementation of exhibition of Batik Lurik and comparative study for Batik Lurik craftsmen although is still not sustainable. The Suggestions that we provide based on the results of the research are to conduct regular monitoring and evaluation of all activities that have been done for the development of the next activity program, improving the promotion and the budgeting.